2006
DOI: 10.1007/s00216-006-0856-9
|View full text |Cite
|
Sign up to set email alerts
|

Precision of Raman depolarization and optical attenuation measurements of sound tooth enamel

Abstract: The demineralization of enamel that is associated with early caries formation affects the optical properties of the enamel. Polarized Raman spectroscopy and optical coherence tomography have been used to detect these changes and potentially offer a means to detect and monitor early caries development. The total optical attenuation coefficient as measured by optical coherence tomography and the polarization anisotropy of the Raman peak arising from the symmetric nu(1) vibration of PO4(3-) at approximately 959 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 10 publications
0
23
0
1
Order By: Relevance
“…[9 -15] Recently, polarized Raman spectroscopy was used to detect early caries in dental enamel. Co and coworkers [16,17] have shown that sound tooth enamel exhibited strong Raman polarization anisotropy, whereas early caries consistently showed a lower degree of Raman polarization anisotropy. Such decrease in the Raman polarization anisotropy detected in the spectra of carious lesions is believed to be due to structural changes in the enamel rods and/or increased photon scattering resulting from the larger pores within the caries lesions.…”
Section: Introductionmentioning
confidence: 99%
“…[9 -15] Recently, polarized Raman spectroscopy was used to detect early caries in dental enamel. Co and coworkers [16,17] have shown that sound tooth enamel exhibited strong Raman polarization anisotropy, whereas early caries consistently showed a lower degree of Raman polarization anisotropy. Such decrease in the Raman polarization anisotropy detected in the spectra of carious lesions is believed to be due to structural changes in the enamel rods and/or increased photon scattering resulting from the larger pores within the caries lesions.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, it is highly probable the that signal intensity and signal attenuation coefficient from the sagittal scan can be utilized as objective parameters for the detection of enamel and dentin demineralization. 23,24 This result is relevant in clinical situations, where an occlusal or facial surface can be sagittally imaged by SS-OCT.…”
Section: Discussionmentioning
confidence: 95%
“…Since the signal intensity and attenuation patterns of SS-OCT images are influenced by the presence of caries, attempts were made to utilize the signal intensity and attenuation coefficient as quantitative parameters for the detection of carious. [20][21][22][23][24] However, limited information is available on the potential use of OCT signals. It was suggested that demineralized enamel resulted in a quick and exponential decline of backscatter signal with depth, due to the increased porosity of the tissue.…”
Section: Introductionmentioning
confidence: 99%
“…These models are based on the assumption that the absorption coefficient is very low compared to the scattering coefficient, otherwise their contributions to the signal attenuation cannot be separated, easily. However, the total attenuation coefficient can also contain sufficient information for diagnostic purposes [135][136][137][138].…”
Section: Measurement Of Bulk Optical Propertiesmentioning
confidence: 99%